Letter: enteral nutrition therapy for the induction of remission in paediatric Crohn's disease—Authors' reply. Issue 10 (20th October 2017) - Feathers, A.; Swaminath, A.; Ananthakrishnan, A. N.; Falzon, L.; Li Ferry, S.
Abstract : Linked Content This article is linked to Dai et al and Swaminath et al papers. To view these articles visithttps://doi.org/10.1111/apt.14337 andhttps://doi.org/10.1111/apt.14253 .